How a plant works - Hardie, Bob; Classroom Video (New South Wales : Classroom Video, 1998)
Covers photosynthesis, simple plants (e.g. mosses), higher plants (e.g. ferns), carnivorous plants and mangrove adaptations
Executive producer, John Davis ; writer, Bob hardie
VCD format
Keywords: Plant hormones; Growth (Plants)